Realizing Ultrahigh Modulus and High Strength of Macroscopic Graphene Oxide Papers Through Crosslinking of Mussel‐Inspired Polymers. (2nd May 2013) - Tian, Ye; Cao, Yewen; Wang, Yu; Yang, Wuli; Feng, Jiachun
<x xml:space="preserve">Abstract</x> Covalently crosslinked graphene oxide papers (GOPs) with enhanced mechanical properties are prepared by a strategy involving crosslinking by means of intercalated polymers. The strength and modulus of the crosslinked GOPs increase by 115% and 550%, respectively, compared to the pristine GOPs. These results broaden the potential applications of graphene, and the crosslinking strategy will open the door to the assembly of other nanometer‐scale materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>